TRAINING THE PROCESSING OF GOAT'S MILK INTO KEFIR AS A PROBIOTIC IMMUNE SYSTEM IMPROVEMENT IN THE TIME OF COVID-19 - Azrul Rizki; Raja Novi Ariska; Surya Asra (Global Science Society, 2021)
Good digestive system will produce a good immune system. A good immune system is needed to prevent the Covid-19 infection. Kefir is a probiotic drink which beneficial for the digestive system. Partners of the activities are PKK women in Sidorejo Village, Kota Langsa. The method consists of three stages; preparation, education and production, and product harvesting. The result of the preparation stage is the delivery of the purpose of activities and agreement of timing of the activity. At the education stage, team explained the benefits of kefir milk for health as well as promising business opportunities, then continued with training of kefir production consists of milk sterilization, starter inoculation, and fermentation. The product is harvested after fermented for 2 x 24 hours. The results obtained good and uncontaminated kefir milk products, which indicates that the PKK women in Sidorejo Village, Kota Langsa has succeeded in making kefir milk products.